FAKTOR-FAKTOR YANG MEMPENGARUHI DERMATITIS KONTAK YANG DILAMIOLEH PEKERJA: Literature Riview - Susilawati Susilawati; Ade Suri Lestari (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Occupational contact dermatitis is dermatitis that arises as a result of contact with chemicals at work, it must be differentiated from non-occupational contact dermatitis, namely contact dermatitis that arises due to contact with materials not related to work such as cosmetics, jewelry, or drugs. The method of this research is this research was conducted using the Literature Review method. The journal used is in accordance with the discussion of "Factors Affecting Workers' Contact Dermatitis." Data collection was taken from Google Scholar by taking 10 articles published in the last five years as a reference. The purpose of this literature study is to find out what factors affect contact dermatitis experienced by workers. Based on the results and discussion of the 10 journals that became the basis for writing this article, it was found that 9 out of 10 journals stated that there was a relationship between age, length of contact, years of service, use of PPE, and personal hygiene with the causative factors of contact dermatitis in workers. Based on research conducted by (Nina Eka Yuliana et al, 2020) states that there is a relationship between personal hygiene and the incidence of dermatitis with a p-value of 0.003 which is in line with research by Lantania Nafsiah (2012). Conclusion Occupational contact dermatitis is dermatitis that arises due to contact with chemicals in the workplace, while the factors of contact dermatitis experienced by workers are age, length of contact, length of work, use of PPE, and personal hygiene